Genetic epidemiology of MODY in the Czech republic: new mutations in the MODY genes HNF-4alpha, GCK and HNF-1alpha - Pruhova, S; Ek, J; Lebl, J; Sumnik, Z; Saudek, F; Andel, M; Pedersen, O; Hansen, T (Diabetologia, 2003)
AIMS/HYPOTHESIS: The aim of this study was to examine the prevalence and nature of mutations in HNF4alpha/MODY1, GCK/MODY2 and HNF-1alpha/MODY3 genes in Czech subjects with clinical diagnosis of MODY. METHODS: We studied 61 unrelated index probands of Czech origin (28 males, 33 females) with a clinical diagnosis of MODY and 202 family members. The mean age of probands was 22.7+/-12.0 years (range, 6-62) and the mean age at the first recognition of hyperglycaemia was 14.7+/-6.0 years (range, 1-25). The promotor and coding regions inclusive intron exon boundaries of the HNF-4alpha, GCK and HNF-1alpha genes were examined by PCR-dHPLC (HNF-1alpha and GCK) and direct sequencing. RESULTS: We identified 20 different mutations in the HNF-4alpha, GCK and HNF-1alpha in 29 families (48% of all families studied), giving a relative prevalence of 5% of MODY1, 31% of MODY2 and 11.5% of MODY3 among the Czech kindred with MODY. Three of 3, 10 of 11 and 1 of 6 of the mutations identified in HNF-4alpha, GCK and HNF-1alpha respectively, were new. CONCLUSION/INTERPRETATION: Of the families 48% carried mutations in the MODY1-3 genes and of the identified mutations 70% were new. In 52% of Czech families with clinical characteristics of MODY, no mutations were found in the analysed genes. This finding shows that the majority of MODY mutations in a central European population are local and that other MODY genes could be responsible for autosomal dominant transmission of diabetes mellitus.
Keywords: Genetic Testing; glukokinasa; hepatocytární jaderný faktor 1-beta; Gene Frequency; Male; Hepatocyte Nuclear Factor 1-alpha; mutace; Child, Preschool; DNA-Binding Proteins; hepatocytární jaderný faktor 1; genetické testování; Adolescent; Česká republika; Child; Glucokinase; transkripční faktory BHLH-Zip; dítě; Adult; Diabetes Mellitus, Type 2; dospělí; hepatocytární jaderný faktor 1-alfa; mužské pohlaví; DNA vazebné proteiny; jaderné proteiny; fosfoproteiny; Phosphoproteins; diabetes mellitus 2. typu; mladiství; Czech Republic; předškolní dítě; frekvence genu; lidé; Transcription Factors; ženské pohlaví; transkripční faktory; Humans; Hepatocyte Nuclear Factor 4; Hepatocyte Nuclear Factor 1; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Mutation; hepatocytární jaderný faktor 4; Female; Nuclear Proteins; lidé středního věku; Hepatocyte Nuclear Factor 1-beta; Middle Aged